1997
DOI: 10.1074/jbc.272.34.21113
|View full text |Cite
|
Sign up to set email alerts
|

Src Kinase Activity Is Regulated by the SHP-1 Protein-tyrosine Phosphatase

Abstract: Activation of the cellular Src tyrosine kinase depends upon dephosphorylation of the carboxyl-terminal inhibitory tyrosine phosphorylation site. Herein we show that Src isolated from human platelets and Jurkat T cells is preferentially dephosphorylated at its inhibitory phosphotyrosine site by the SHP-1 tyrosine phosphatase. The data also revealed association of Src with SHP-1 in both platelets and lymphocytes and the capacity of Src to phosphorylate SHP-1 and interact with the SHP-1 NH 2 -terminal SH2 domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
125
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 50 publications
2
125
0
1
Order By: Relevance
“…The above conclusion predicts that if the autophosphorylation of Src is kept at a minimal level, it would be inactivated by a sub-stoichiometric amount of Csk. As demonstrated in Figure 3, PTP 1B readily dephosphorylates the autophosphorylation site of Src, but it was reported not to dephosphorylate the phosphorylated Y r (Somani et al, 1997). We took advantage of this apparent speci®city of PTP 1B to examine how the presence of PTP 1B would change Csk inactivation of Src when a sub-stoichiometric amount of Csk was used (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above conclusion predicts that if the autophosphorylation of Src is kept at a minimal level, it would be inactivated by a sub-stoichiometric amount of Csk. As demonstrated in Figure 3, PTP 1B readily dephosphorylates the autophosphorylation site of Src, but it was reported not to dephosphorylate the phosphorylated Y r (Somani et al, 1997). We took advantage of this apparent speci®city of PTP 1B to examine how the presence of PTP 1B would change Csk inactivation of Src when a sub-stoichiometric amount of Csk was used (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Further study is required to verify this role in vivo and understand the basis for the preference for PTP 1B. Several PTPs have been proposed to speci®cally dephosphorylate the Y r of Src, including SH2 domain-containing PTP (Somani et al, 1997) and trans-membrane PTP a (Zheng et al, 1992) and PTP l (Chappel et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SH-PTP1 and SH-PTP2 can associate in vitro and in vivo with the EGF receptor (Tomic et al, 1995), and SH-PTP2 has been detected in association with Src in a human colon carcinoma cell line (Peng and Cartwright, 1995), although biological e ects of these associations have not been demonstrated. In addition, SH-PTP1 is capable of dephosphorylating Src in vitro at Tyr530 and there is a positive correlation between the expression of SH-PTP1 and Src kinase activity in vivo in mouse thymocytes (Somani et al, 1997). The phosphatases LAR and PTP1B have been reported to be overexpressed in human breast epithelial cells transformed with an activated rat Neu receptor (Zhai et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evidence has been presented that also implicates SHP-1 in the dephosphorylation and activation of c-Src (Somani et al, 1997). Interestingly, the authors found that although SHP-1 was capable of dephosphorylating both Tyr(416/419) and Tyr(527/ 530), it appeared to exert a more pronounced e ect on Tyr(527/530), suggesting that SHP-1 may be more speci®c for Tyr(527/530).…”
Section: Shp-1mentioning
confidence: 97%
“…Although the c-Src protein levels were similar in both types of motheaten mice and normal mice, there was a markedly lower level of c-Src tyrosine kinase activity in the motheaten and viable motheaten mice, accompanied by increased levels of phosphorylation on Tyr(527/530). In addition, dominant-negative SHP-1 expressed in HEY ovarian epithelial cancer cells resulted in reduced dephosphorylation of SHP-1 substrates and reduced c-Src kinase activity (Somani et al, 1997).…”
Section: Shp-1mentioning
confidence: 99%